Public Awareness of the Risk Factors for Intestinal Worm Disease in Koncang Pandeglang Vilagge, Banten and the Review from an Islamic View - Saleh, Muhammad Fathurrahman; Hardjanti, Ambar; Arifandi, Firman (Junior Medical Journal, 2024)
Introduction: Infection with soil-transmitted helminth worms (STH) in the world reaches more than 1.5 billion people or 24% of the world's population. Indonesia is a tropical country with a high incidence of STH in several regions, especially at the age of children. The high incidence of helminthiasis is influenced by poor hygiene behavior and lack of knowledge about worms. The purpose of this study was to determine the awareness of the people of Koncang Village, Pandeglang on the risk factors for intestinal worms.Methodology: This research is a quantitative descriptive study with a cross sectional approach. The population of this study was the community of Koncang Village, Pandeglang Regency, which consisted of 49 people. The data used is primary data by using a questionnaire through interviews. The technique used in data analysis is the Chi-square test.Results: The results showed that the majority of knowledge, attitudes, and behavior towards intestinal helminth disease were good. Based on statistical tests, there is a relationship between knowledge and behavior towards intestinal worms with a p-value of 0.00 (p <0.05). In addition, there is also a relationship between attitudes and behavior towards intestinal worms with a p-value of 0.03 (p <0.05).Conclusion: There is a significant relationship between knowledge and attitudes with behavior related to intestinal worms. The community should continue to increase their knowledge and be assisted by health workers through health promotion.